THE USE OF POW-TEGA IN TEACHING SPEAKING TO THE TENTH GRADE STUDENTS OF THE SENIOR HIGH SCHOOL PGRI 2 OF PALEMBANG - Herlina, Herlina; Marleni, Marleni; Putri, Dini Utami (English Community Journal, 2020)
The problem of this study was: “Is there a significant difference between the students who taught by PowTega strategy and those who are not to the tenth grade students of the Senior High School PGRI 2 of Palembang?”. The objective of the study was to find out whether or not there is there a significant difference between the students who taught by Pow-Tega strategy and those who are not to the tenth grade students of the Senior High School PGRI 2 of Palembang. This study applied an experimental control group design with two classes. the prettest-posttest group design. The population of the study was all of the tenth grade students of Senior High School PGRI 2 of Palembang consisting of 8 classes with 228 students as the whole number. The sample was 72 students divided into two classes: experimental and control groups. The sample was taken by using cluster random sampling. In collecting the data, the writer used speaking or oral tests. The tests were given to the students about descriptive text which focus about describing country. Based on the result of the data analysis, the findings of the study showed that the speaking scores of the tenth grade students taught through Power Teaching Game (Pow-Tega) Strategy were higher than those of the ones taught through conventional method of Senior High School PGRI 2 of Palembang. In experimental group, the highest post-test score was 74, the lowest post-test score was 66, and the average was 66.91 while 70 was the highest score in control group, the lowest post-test score was 64, and the average was 67.19 Ho was rejected and Ha was accepted. It means that there was significant difference in teaching speaking skill to the tenth grade students of Senior High School PGRI 2 of Palembang who are taught by using Pow-Tega strategy and those who are not. Besides, proved that the students’ scores in post-test were higher than in the pre-test. It implies that the use of Pow-Tega strategy brought improvement to students’ speaking skill and it could be used as an alternative strategy in teaching speaking.